Terhadap Kualitas Layanan Pada Angkutan Kota (Bemo Kuning) di Mataram - Rizka milania ulfah; Laili Hurriati (Fakultas Ekonomi Universitas Islam Al-Azhar, 2019)
The traffic congestion is one of the problems currently faced by the city of Mataram. This is due to an increase in the number of private vehicle ownership each year and is accompanied by the unwillingness of the people of Mataram to drive using public transportation. In addition, the number of public transportation fleets that are still operating in the city of Mataram especially Angkot (Bemo kuning) continues to decrease each year and this is accompanied by the attention of the city government which is still relatively minimal to overcome the problem. The purpose of this study is to obtain data and information related to the level of performance of urban transportation (Bemo Kuning) in terms of the level of public satisfaction with the quality of services provided at City Transport (Bemo Kuning) in Mataram. This research is a descriptive study with a quantitative approach and using the questionnaire as a data collection tool. An analyzer used to measure the level of customer satisfaction with the performance of the Bemo kuning is a quadrant analysis. The results of the study, showed that the performance of angkot bemo kuning in Mataram is in the quadrants I, II, III and IV. That is shown by the Cartesius diagram.